TRANSFER PRICING PRACTICES: STUDY IN MANUFACTURING COMPANIES IN INDONESIA - Jannah, Vika Miftahul (Jurnal Al-Iqtishad, 2023)
This study aims to examine whether there is an influence between taxes, bonus mechanisms, profitability, tunneling incentives on transfer pricing. The data used in this research is secondary data. This type of research is quantitative. The number of samples used was 147 companies with three years of observation, namely the 2018-2020 timeframe. research criteria using purposive sampling method. This study uses multiple linear regression analysis techniques. The results of this study indicate that: a) the calculated t value is 2.263 while the t table is 1.97681 with a significance of 0.025 which is less than = 0.05 so it can be concluded that taxes partially have a significant effect on transfer pricing. b) the t count is -4.703 while the t table is 1.97681 with a significance of 0.000 which is less than = 0.05 so it can be concluded that the bonus mechanism partially has a significant effect on transfer pricing. c) the calculated t value is -0.295 while the t table is 1.97681 with a significance of 0.769 which is greater than = 0.05 so it can be concluded that Profitability partially has no significant effect on Transfer Pricing. d) the calculated t value is -6.113 while the t table is 1.97681 with a significance of 0.000 which is less than = 0.05 so it can be concluded that Tunneling Incentive partially has a significant effect on Transfer Pricing.